Comparative investigation of the transport and deposition of nebulized particles in pediatric mouth-throat airways with tonsil hypertrophy at different severity levels - Yang, Feilun; Ma, Ruiping; Wang, Yusheng; Li, Zehui; Shi, Yewen; Feng, Xin; Zheng, Guoxi; Ren, Xiaoyong; Cheng, Shaokoon; Dong, Jingliang; Zhang, Ya (International journal of pharmaceutics, 2025)
[Display omitted] Pediatric allergic asthma necessitates efficient aerosol drug delivery through the mouth-throat (MT) airway. Tonsil hypertrophy (TH), a common comorbidity, causes oropharyngeal obstruction, potentially compromising inhalation therapy. This study quantitatively investigated the impact of TH severity on lung delivery of nebulized aerosols. Five patient-specific pediatric MT models were reconstructed from computed tomography (CT) scans of grade IV TH (IV-TH) patients. For each model, four virtual severities (I-TH to IV-TH) and a post-tonsillectomy “Normal” model were created, representing 0 % to > 75 % oropharyngeal obstruction. Airflow and particle transport were simulated using computational fluid-particle dynamics (CFPD) approach at inhalation rates of 8–15 L/min, with particle sizes ranging from 1 to 30 μm. Increasing TH severity progressively narrowed the oropharynx, elevating airway resistance and altering deposition patterns. The optimal particle size for targeted drug delivery decreased with worsening obstruction. In IV-TH models, droplets in the 13–30 μm range achieved over 75 % of the maximum deposition efficiency in the tonsillar target region. The drug delivery rate through the MT airways exhibited significant inter-subject variability (up to ∼ 25 %), directly correlated with the degree of oropharyngeal narrowing. The findings of this study demonstrate that the severity of tonsillar hypertrophy strongly influences the deposition patterns of nebulized aerosols, highlighting the need for approach. a precision medicine approach. For children with IV-TH, larger particles (13–30 μm) are optimal for targeting the oropharyngeal region, while less obstructed airways require finer aerosols for lung delivery. These findings provide an aerodynamic basis for tailoring inhalation therapy to individual pediatric airway anatomy.